2003
DOI: 10.1111/j.1654-109x.2003.tb00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of sheep grazing in the restoration of semi‐natural meadows in northern Finland

Abstract: Abstract. The biodiversity of species‐rich semi‐natural meadows is declining across Europe due to ceased management. In this study we aimed to find out how successfully the local species richness of an overgrown semi‐natural mesic meadow could be restored by sheep grazing after a long period of abandonment. The cover of vascular plant species in grazed plots and ungrazed exclosures was studied for five years and the responses of different functional plant groups were followed (herbs vs grasses, tall vs short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 23 publications
5
27
0
Order By: Relevance
“…Huhta et al 2001;Hellström et al 2003). Our correlation analyses support the assumption that litter accumulation has a negative effect on seedling recruitment and consequently restoration mowing and removal of litter by raking may promote seedling recruitment.…”
Section: Discussionsupporting
confidence: 81%
“…Huhta et al 2001;Hellström et al 2003). Our correlation analyses support the assumption that litter accumulation has a negative effect on seedling recruitment and consequently restoration mowing and removal of litter by raking may promote seedling recruitment.…”
Section: Discussionsupporting
confidence: 81%
“…In accordance with our hypothesis 1 we assume that these sites can maintain their structure due to positively related disturbance effects, which are in particular grazing and trampling in moderate intensities. Hellström et al (2003) observed in a study with sheep-grazed (formerly abandoned) and ungrazed plots in semi-natural grasslands in Finland an increase of species numbers by nearly 30% in case of sheep grazing. Our findings suggest that this may apply only if ungrazed areas are grazed and if there are no further, stronger disturbance effects like high rabbit densities in the community, which are able to counteract the positive impact of sheep grazing.…”
Section: Moderate Disturbance (Sheep Grazing)mentioning
confidence: 89%
“…Thus, due to impoverishment of species pools attributable to habitat loss and dispersal limitation, the results of restoration by merely using reintroduced management have often been relatively modest (Hellström et al 2003;Huhta et al 2001;Walker et al 2004). Therefore, the introduction of species belonging to regional species pools has lately been increasingly favoured as an effective restoration tool.…”
Section: Introductionmentioning
confidence: 98%